Feminisation of UK General Practice: a challenge for the Defence Medical Services?. Issue 2 (18th February 2014) - Withnall, Richard D J; Graham, D J M; Morris, L E; Wallace, M
Abstract : Background: The Defence Medical Services (DMS) primarily recruits its trained General Practitioners (GPs) from the NHS and since 1970, the number of men entering medicine has doubled whereas the number of women has increased 10-fold; female GPs will outnumber their male counterparts by 2017. This study performs a quantitative assessment of the potential impact of feminisation of UK General Practice upon the DMS recruitment and workforce planning. Methods: General Medial Council General Practice Certificate of Completion of Training (GMC GP CCT) data were analysed to identify any change in the percentage of male and female GP Specialty Training Registrars successfully completing GP vocational training between 2007 and 2012, thus becoming potentially recruitable into the DMS as independent GPs. Results: A 3% increase was seen in the number of women achieving GMC GP CCT between 2007 and 2012 (p=0.015). The percentage of DMS GP Specialty Training Registrars (GPStRs) gaining their GMC GP CCT in 2012 who were women (25%) was about half that seen nationally (59%). A lack of 2007 by-sex GMC GP CCT data for DMS GPStRs prevented a comparison with 2012. Conclusions: The national increase of only 3% infers feminisation of UK General Practice is not an immediate challenge for the DMS. Nevertheless, as feminisation of the UK GP workforce is expected to continue, the future cohort from whom the DMS will recruit its GPs is likely to contain increasing numbers of women. With the return to contingency, the DMS may wish to consider the implications of increasing numbers of female GPs upon service delivery in the UK and overseas, and explore more flexible medical employment models.